(untitled) (Research, Society and Development, 2019)
Introduction: Enteral nutritional therapy (ERT) is essential to restore or maintain the patient’s nutritional status. However, it may not guarantee the reach of nutritional needs and may generate several complications. Aiming at better patient care, quality tools have been created as quality indicators in enteral nutritional therapy (IQTNE). Objectives: To analyze IQTNE in an intensive care unit (ICU). Methods: This was a retrospective study composed of data collected during eight months from the medical charts of patients under ERT who were admitted to an ICU of a private hospital. The IQTNE analyzed were: (1) frequency of nutritional screening; (2) frequency of days of adequate energy administration; (3) frequency of days of adequate protein administration; (4) frequency of diarrhea; (5) inadvertent output frequency of nutrition probe; (6) frequency of nutrition probe obstruction and (7) adequacy rate of volume infused over prescribed. Results: The sample included data from 122 patients under ERT with mean age of 76.9 ± 16.4 years and 29.9 ± 28.6 days of hospitalization. The IQTNE (1) showed a mean of 97.3 ± 3.1%, IQTNE (2) 88.1 ± 3.8%, IQTNE (3) 89.8 ± 4.8%, IQTNE (4) 9 , IQTNE (5) 3.9 ± 2.2%, with inadequacy in 25% of the months analyzed, IQTNE (6), 0.8% ± 1.5% and the IQTNE (7) obtained 94.3 ± 3.3% of adequacy. The observed complications negatively influenced the adequacy of the instituted ERT. Conclusion: On average, all IQTNs analyzed reached the pre-established goal; however, attention should be given to the symptoms of diarrhea and inadvertent outflow of the nutrition tube.